2011
DOI: 10.1002/cctc.201000368
|View full text |Cite
|
Sign up to set email alerts
|

A Ru–vinylvinylidene Complex: Straightforward Synthesis of a Latent Olefin Metathesis Catalyst

Abstract: Ruthless ruthenium complex: A novel ruthenium vinylvinylidene complex has been synthesized and characterized. The latent catalyst can be activated at elevated temperatures to perform ring opening metathesis polymerization (ROMP, see figure) and ring closing metathesis reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 64 publications
1
13
0
Order By: Relevance
“…1b,c The systematic exploration of the electronic effects of the alkylidene group on the catalytic performance revealed that electron withdrawing para-substituents not only withdraw electron density from the aromatic ring but also from the RuQC center, which resulted in a fast initiating catalyst. 13 The direct treatment of propargylic alcohols with RuCl 2 (PPh 3 ) 3 gave rise to alkenylidene 14 (vinylidene, 15 allenylidene 10,16 and indenylidene 9a,17 ) ruthenium complexes. The latter method is a much more convenient way to obtain the ruthenium catalysts 3d compared with their benzylidene analogue 1a.…”
Section: Introductionmentioning
confidence: 99%
“…1b,c The systematic exploration of the electronic effects of the alkylidene group on the catalytic performance revealed that electron withdrawing para-substituents not only withdraw electron density from the aromatic ring but also from the RuQC center, which resulted in a fast initiating catalyst. 13 The direct treatment of propargylic alcohols with RuCl 2 (PPh 3 ) 3 gave rise to alkenylidene 14 (vinylidene, 15 allenylidene 10,16 and indenylidene 9a,17 ) ruthenium complexes. The latter method is a much more convenient way to obtain the ruthenium catalysts 3d compared with their benzylidene analogue 1a.…”
Section: Introductionmentioning
confidence: 99%
“…A convenient way to obtain a ruthenium based alkylidene catalyst (vinylidene [17], allenylidene [6c,18] and indenylidene [7a,12,19]) is the direct treatment of non-hazardous propargylic alcohols with RuCl 2 (PPh 3 ) 3 [20]. However, the ruthenium indenylidene catalysts were generally preferred among these three families since they showed a relatively more active performance in olefin metathesis reactions in comparison to their vinylidene or allenylidene analogues [15b].…”
Section: Resultsmentioning
confidence: 99%
“…General procedure for RCM of diethyl diallylmalonate (DEDAM). Analogous to the procedure described in [ 72 ], DEDAM (14.6 μL, 60 μmol) was added via microliter syringe through a septum to a stock solution of the catalyst (in C 6 D 6 for 9 and 11 , CDCl 3 for 12 – 1.0 mM, 0.60 mL, 0.6 μmol) in a NMR tube. The substrate conversion was monitored at 20 °C via 1 H NMR spectroscopy by integration of the sufficiently separated multiplet signals at δ 2.78 ppm (m, allyl-C H 2 , DEDAM) and 3.13 ppm (m, ring-C H 2 , cyclopentene derivative).…”
Section: Methodsmentioning
confidence: 99%
“…General procedure for the RCM of diallylmalonic acid (DAMA). Analogous to the procedure described in [ 72 ], the catalyst (8 μmol) and DAM (36.8 mg, 0.20 mmol) were dissolved in the 0.1 M HCl aq (2.0 mL) under inert gas conditions and the solution was heated to 50 °C under stirring. An aliquot (0.3 mL) was taken after 30 min and 60 min, quenched with ethyl vinyl ether, dried under vacuum, and the monomer conversion was monitored via 1 H NMR spectroscopy (300.1 MHz, 20 °C, D 2 O) by integration of the signals δ 2.58 (DAMA-CH 2 ) and δ 2.98 ppm (cyclopentene-C H 2 ).…”
Section: Methodsmentioning
confidence: 99%